The Culture-Transmission Motive in Minorities: An Online Survey of Adolescents and Young Adults with an Immigrant Background in Germany. (26th December 2013) - Mchitarjan, Irina; Reisenzein, Rainer
Abstract : Central assumptions of a theory of cultural transmission in minorities proposed by the authors were tested in an online survey of adolescents and young adults with Russian and Turkish immigrant background in Germany (N = 55 ). The results support most hypotheses. In particular, evidence was obtained for the existence of the culture-transmission motive postulated by the theory: the appreciation of the culture of origin and the desire to maintain it and pass it on to the next generation. In addition, evidence was obtained for the anchoring of the culture-transmission motive in more basic motives, its relative stability, and its motivating function for pedagogical activities and wishes regarding cultural transmission, including the wish for culture-specific education in public schools.